Health system determinants of vision protection practices among monocular patients attending a referral eye hospital in Kenya - Koome, Peter Mutuma; Kerochi, Atei; Maathai, Ronald; Omoto, Alloysius Luambo (International Journal Of Community Medicine And Public Health, 2026)
Background: Monocular patients are at increased risk of bilateral blindness as soon as they lose their remaining eye. Despite the importance of protective eye-care behaviors in preserving residual vision, evidence on health system factors influencing vision protection among monocular patients in low- and middle-income countries remains limited. The study assessed health system determinants of vision-protection practices among monocular patients attending the Thika Level Five Hospital Eye Clinic, Kenya. Methods: The study used a cross-sectional, analytical design. A well-structured questionnaire was used to survey 125 monocular patients. Data were analyzed using SPSS version 25 using descriptive statistics, chi-square tests, and binary logistic regression at a 95% confidence interval, with p<0.05 considered statistically significant. Results: Response rate was 95.2% (119/125). Overall, 58.6% of respondents demonstrated poor vision protection practices. Binary logistic regression analysis demonstrated that respondents residing far from the health facility were significantly more likely to exhibit poor protection practices (OR=12.604, 95% CI: 2.441-65.083, p=0.003). Similarly, respondents who had not received health education on vision protection were significantly more likely to demonstrate poor practices (OR=5.386, 95% CI: 1.697-17.097, p=0.004). Inaccessible ophthalmic services and poor caregivers’ communication were also significantly associated with poor protection behaviors (p<0.05). Conclusions: Poor vision protection practices remain highly prevalent. Long distances to hospitals, inadequate health education, and inaccessible eye services significantly influence the adoption of vision protective practices. Decentralizing services through mobile eye clinics, strengthening patient-centered education, and improving the accessibility of ophthalmic services may improve preventive behaviors and reduce avoidable blindness among monocular patients.